1998
DOI: 10.1007/s001470050458
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence-free survival after liver transplantation for small hepatocellular carcinoma

Abstract: Recurrence-free survival (RFS) in patients with small hepatocellular carcinoma (HCC) after orthotopic liver transplantation (OLT) was analyzed. From 1988 until 1996, 725 OLTs were performed in 669 patients. In 52 adults, HCC was confirmed histologically. OLT was limited to patients with small (< 5 cm) HCC with a maximum number of three nodules. Actuarial survival for these 52 patients at 1 and 5 years is 88% and 71%. RFS was defined as time until death without recurrence time until follow up with a diagnosis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 12 publications
1
14
0
Order By: Relevance
“…Several studies have identified patient and tumor-related variables associated with prognosis following oLTX (4,5,7,8,(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). Important variables associated with prognosis in one or more of the studies included tumor number, tumor size, whether tumors were bilobar, stage of disease, degree of differentiation, macrovascular and microvascular invasion, and extra-hepatic spread.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have identified patient and tumor-related variables associated with prognosis following oLTX (4,5,7,8,(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). Important variables associated with prognosis in one or more of the studies included tumor number, tumor size, whether tumors were bilobar, stage of disease, degree of differentiation, macrovascular and microvascular invasion, and extra-hepatic spread.…”
Section: Discussionmentioning
confidence: 99%
“…Excellent outcomes after liver transplantation for patients with HCC within the Milan criteria have subsequently been reported from other centers. [5][6][7][8] Our initial experience with 9 consecutive patients transplanted with HCC, in whom no recurrences were seen, suggested that the criteria may be too restrictive and that patients with more advanced disease may also benefit from liver transplantation. Other groups have further investigated the impact of tumor characteristics on tumor recurrence and patient survival.…”
mentioning
confidence: 99%
“…The 5-year tumor recurrence-free survival rate after resection of early HCC within the Milan criteria in Child A cirrhotic patients was 40-48% [13,18,45] , as compared to that of 60-80% after liver transplantation [18,44,48] . The lower tumor recurrence rate after transplantation is expected because it eliminates multicentric hepatocarcinogenesis in the cirrhotic liver.…”
Section: Comparison Of Survival Results Of Resection and Transplantationmentioning
confidence: 99%